2017
DOI: 10.2147/cmar.s111673
|View full text |Cite
|
Sign up to set email alerts
|

Prospect of the use of checkpoint inhibitors in hepatocellular cancer treatments

Abstract: Hepatocellular cancer (HCC) is a very fatal disease due to limited therapeutic options as well as due to its association with underlying chronic liver disease in the majority of cases. The immune evasion in HCC signifies a major barrier to the delivery of effective immunotherapy. Sorafenib is the only Food and Drug Administration-approved drug available with an overall response rate of 2%–3% and overall survival of 2.8 months. Chemotherapy has not been used routinely because of the relative refractoriness of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…These higher rates of Grade 3‐4 adverse events likely reflect additive effects of tissue autoantigen release as a result of tumour infiltration and/or viral damage in conjunction with ICI‐induced increase of autoreactive T cell activity. There have been a growing number of published studies designed to determine the effects of ICIs for the treatment of HCC . In one clinical study, HCC patients undergoing CTLA‐4 blockade with tremelimumab who were infected with HCV demonstrated a relatively good liver adverse event profile with only transient elevations of serum aminotransferases after the first dose of therapy …”
Section: Clinical Trials Of Icis: Results Of Risk For Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…These higher rates of Grade 3‐4 adverse events likely reflect additive effects of tissue autoantigen release as a result of tumour infiltration and/or viral damage in conjunction with ICI‐induced increase of autoreactive T cell activity. There have been a growing number of published studies designed to determine the effects of ICIs for the treatment of HCC . In one clinical study, HCC patients undergoing CTLA‐4 blockade with tremelimumab who were infected with HCV demonstrated a relatively good liver adverse event profile with only transient elevations of serum aminotransferases after the first dose of therapy …”
Section: Clinical Trials Of Icis: Results Of Risk For Hepatotoxicitymentioning
confidence: 99%
“…There have been a growing number of published studies designed to determine the effects of ICIs for the treatment of HCC. [59][60][61][62][63][64] In one clinical study, HCC patients undergoing CTLA-4 blockade with tremelimumab who were infected with HCV demonstrated a relatively good liver adverse event profile with only transient elevations of serum aminotransferases after the first dose of therapy. 65…”
Section: Studies With Single-agent Ici Treatment Protocolsmentioning
confidence: 99%
“…Overexpression of these checkpoints may lead to cytotoxic T cell exhaustion and a state of immune tolerance to HCC cells. Co-culture studies have demonstrated that PDL-1 or PD-1 blockade through monoclonal antibodies resulted in cytotoxic T cell recovery and improved effector responses (46).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Moreover, high daily doses (over 800 mg) result in a range of side effects and heavy financial burden. 11 Our aim is to develop novel approaches for increasing the efficacy and safety of molecular targeted agents.…”
Section: Introductionmentioning
confidence: 99%